Instilling values to children in conflict with the law in a youth facility - Aguilar, Maria Virginia G. (Animo Repository, 2016)
This study investigates how values are instilled to children in conflict with the law (CICL) in a Philippines youth facility through the houseparent-resident relationship. Although a wealth of literature has examined the condition of child residents in youth rehabilitation institutions, little is known about the relationship between the child residents and the houseparents assigned to care for them, particularly, how the values the houseparents instill in the children impacts on their rehabilitation. Through an ethnographic study of a child facility and in-depth interviews of the CICL residents and their houseparents, the study presents a rich description of the kind of relationship between these carers and their wards. The totalizing effect of the institution is mitigated by the genial relationship between the houseparents and the child residents. In particular, the Filipino values of personalism as applied by the houseparents in their parenting tasks positively impacts on the child residents they are caring for. The findings gathered from this study will provide critical information on what values the social workers, caregivers, houseparents and other staff of a youth facility should impart to the CICL to help achieve the facility's rehabilitative goals. © SAGE Publications.